The Belko experiment [videorecording (DVD)] - Gallagher, John, Jr., 1984-; Goldwyn, Tony; Arjona, Adria, 1992- (20th Century Fox Home Entertainment, 2017)
In a twisted social experiment, a group of 80 Americans are locked in their high-rise corporate office in Bogota, Colombia, and ordered by an unknown voice coming from the company's speaker system to participate in a series of murderous moral decisions.